1, 4- and 1, 5-di(N-phthalimidomethyl)-1, 2, 3-triazoles: crystal structures and density functional theory studies of the alkyne and azide precursors. (1st May 2016) - López-González, Ricardo; Bautista-Renedo, Joanatan; Martínez-Otero, Diego; Reyes, Horacio; González-Rivas, Nelly; Cuevas-Yañez, Erick
Two new di(phthalimidomethyl)-1, 2, 3-triazole derivatives have been synthesised using 1, 3-dipolar-cycloadditions under thermal and copper catalysed conditions from N-(azidomethyl)phthalimide and N-prop-2-ynylphthalimide. The molecular structure of both starting materials was studied by X-ray crystallography. A complete DFT analysis of the alkyne and azide compounds was carried out.